PENGGUNAAN SIX SIGMA PADA PEMERIKSAAN JUMLAH LEUKOSIT DI RSUD PANEMBAHAN SENOPATI BANTUL - Magdalena Putri Iriyanti Dumatubun; Hieronymus Rayi Prasetya; Nurlaili Farida Muhajir (Journal of Indonesian Medical Laboratory and Science, 2021)
Internal quality assurance is a prevention and control activity that must be carried out by the laboratory continuously and covers all aspects of laboratory examination parameters. Hematology examination in the laboratory is carried out using a Hematology analyzer, but this tool has limitations, one of which is that it can make leukocyte count reading errors. In order for the results of the tool to be reliable, it is necessary to carry out quality control on the hematology analyzer. The use of Westgard multirule is commonly used in laboratories, but the application of six sigma is still very rarely used, especially in the field of hematology. This research aims to know the internal quality control of the analytical stage of the Hematology analyzer for the leukocyte count based on the analysis of Westgard and Six sigma. This type of research is descriptive research. The sample in this study is the control value data for the examination of the leukocyte count for 1 month at Panembahan Senopati Hospital. The data were analyzed using the Westgard rules and Six sigma. At low level, 13s deviation (random error) is obtained. At the normal level, there is a deviation of 12s (warning). At high level 12s deviation is obtained (warning). The sigma scale at all control levels shows a scale above 6. Analysis based on six sigma for leukocyte count showed an average of 7.16 sigma which indicates that leukocyte examination using a hematology analyzer has an accuracy of 99.9%.